2017
DOI: 10.18805/asd.v37i03.8993
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of farmers towards Zero – Tillage Technology in Haryana

Abstract: A study was conducted in two districts i.e. Fatehabad from South-West zone and Karnal from North- East Zone of Haryana state .A list of all the villages (Zero tillage technology users) in each selected village was prepared. Twenty farmers (having small, medium and large size of land holdings) were selected by using random sampling techniques from each village. Therefore, the sample constituted for the proposed study was one hundred and forty farmers/respondents to collect the information for the purposively st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is also evident that the lead farmers serving as role models was one of the most effective ways in information distribution and community-level support for CASI implementation, because they spoke in basic and local languages and were aware of local idiosyncrasies. Previous research has shown that awareness of ZT has a favorable impact on attitudes about CASI, resulting in adoption (Kumar and Godara, 2017). In addition to overcoming technological challenges directly related to field implementation of the technology and strengthening of service providers, and local agri-businesses were also found to be crucial for scaling, as also seen in Landers's (2001) research.…”
Section: Discussionmentioning
confidence: 76%
“…It is also evident that the lead farmers serving as role models was one of the most effective ways in information distribution and community-level support for CASI implementation, because they spoke in basic and local languages and were aware of local idiosyncrasies. Previous research has shown that awareness of ZT has a favorable impact on attitudes about CASI, resulting in adoption (Kumar and Godara, 2017). In addition to overcoming technological challenges directly related to field implementation of the technology and strengthening of service providers, and local agri-businesses were also found to be crucial for scaling, as also seen in Landers's (2001) research.…”
Section: Discussionmentioning
confidence: 76%